Enhanced hardness of nanocarbon films deposited on cemented tungsten carbide substrates by coaxial arc plasma deposition owing to employing silicon-doped graphite targets. (3rd July 2019) - Egiza, Mohamed; Murasawa, Kouki; Ali, Ali M.; Fukui, Yasuo; Gonda, Hidenobu; Sakurai, Masatoshi; Yoshitake, Tsuyoshi
Abstract: 1 at% Si-doped nanocrystalline diamond/amorphous carbon (NCD/a-C) composite films were deposited on cemented carbide (WC–Co) substrates by coaxial arc plasma deposition. The doping of Si evidently degraded the hardness of films directly deposited on the substrates due to catalytic effects of diffused Co atoms into the films. On the other hand, by employing undoped NCD/a-C buffer layers, the Co diffusion was suppressed and the hardness was enhanced from 42 to 60 GPa. It was found that the Si doping enhances the formation of C–C sp 3 bonds, which resulted in the hardness enhancement in the case of suppressing the Co diffusion by insertion of undoped NCD/a-C buffer layers.